2020
DOI: 10.1021/acs.joc.0c00055
|View full text |Cite
|
Sign up to set email alerts
|

Visible- and UV-Light-Induced Decarboxylative Radical Reactions of Benzoic Acids Using Organic Photoredox Catalysts

Abstract: Photoinduced decarboxylative radical reactions of benzoic acids with electron-deficient alkenes, diborane, and acetonitrile under organic photoredox catalysis conditions and mild heating afforded adducts, arylboronate esters, and the reduction product, respectively. The reaction is thought to involve single-electron transfer promoted the generation of aryl radicals via decarboxylation. A diverse range of benzoic acids were found to be suitable substrates for this photoreaction. Only our two-molecule organic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…Yoshimi and co‐workers, recently reported that a photoredox system based on biphenyl (BP)/1,4‐dicyanonaphthalene (DCN) promotes decarboxylative borylation of benzoic acids with bis(pinacolato)diboron (B 2 pin 2 ) under ultraviolet‐light irradiation (Scheme 96). [383] Electron‐rich, ‐neutral, as well as ‐poor phenylboronate esters were synthesized, although only in moderate yields. The authors proposed that under ultraviolet‐irradiation a SET process between excited‐state DCN* and BP initially occurs to deliver the anion radical [DCN] .− and the radical cation [BP] .+ .…”
Section: Decarboxylative C−b Bond Formationmentioning
confidence: 99%
“…Yoshimi and co‐workers, recently reported that a photoredox system based on biphenyl (BP)/1,4‐dicyanonaphthalene (DCN) promotes decarboxylative borylation of benzoic acids with bis(pinacolato)diboron (B 2 pin 2 ) under ultraviolet‐light irradiation (Scheme 96). [383] Electron‐rich, ‐neutral, as well as ‐poor phenylboronate esters were synthesized, although only in moderate yields. The authors proposed that under ultraviolet‐irradiation a SET process between excited‐state DCN* and BP initially occurs to deliver the anion radical [DCN] .− and the radical cation [BP] .+ .…”
Section: Decarboxylative C−b Bond Formationmentioning
confidence: 99%
“…Inspired by visible-light-induced decarboxylation processes, the group of Yoshimi recently extended this concept to the intermolecular decarboxylative radical addition reaction between electron-poor alkenes and aryl carboxylic acids under mild conditions (30 C) (Kubosaki et al, 2020) (Scheme 29). As a result, a wide variety of electron-poor alkenes, such as acrylonitrile, acrylamide, acrylate, and phenyl vinyl sulfone, coupled smoothly with benzoic acids upon visible light or UV irradiation.…”
Section: Reviewmentioning
confidence: 99%
“…However, even with the low barrier for radical aromatic decarboxylation, other reactions such as hydrogen atom abstraction (HAT) and back electron transfer (BET) can be even faster [2] and result in undesired reactivity. Radical decarboxylation of benzoic acids has been successfully used to react with reactive radical acceptors such as (hetero)arenes, [21] acrylates, or diboron species, [22] but not to make C−O bonds, even with prior activation to activated esters [23]…”
Section: Figurementioning
confidence: 99%
“…Both electron‐poor and electron‐rich substrates, such as 4‐cyanobenzoate ( 3 ) and 3,5‐dimethylbenzoate ( 13 ) can outcompete TC to afford the corresponding phenols (Table 1). Electron neutral benzoates, which are often problematic for thermal decarboxylation due to the lack of electronic bias, [16] or electron deficient benzoates, which are often problematic for oxidative radical decarboxylation due to their high oxidation potential, [21b, 22] performed well. Heteroaryl carboxylates, such as isonicotinic carboxylates ( 6 , 14 ) and quinoxaline‐2‐carboxylate ( 15 ), are also compatible.…”
Section: Figurementioning
confidence: 99%